(untitled) (Research, Society and Development, 2022)
This article deals with assessment as a pedagogical act, considering the learning and development of students. In its wake, the importance of error as a didactic factor in learning is addressed. In this sense, it aims to reflect on constructive error as a component of the pedagogical act, from the perspective of learning assessment. As a method, it uses bibliographic research, in an approach characterized as qualitative. The study is justified in order to answer how error can be considered as a component of the pedagogical act of learning assessment. The results show that constructive error, as a way of evaluating, is configured as one of the components of the pedagogical act of learning evaluation. It is concluded as urgent the need to understand that the errors presented in the evaluation processes can be interpreted not only as a thermometer to measure who was better or worse, but as a starting point for progress. As a future contribution, there is a possibility of promoting an improvement in student learning, thus assuming a pedagogical function.